Analysis of systemic risk factors of occipital stroke-related vision loss - Indra Tri Mahayana; Nyssa Alexandra Tedjonegoro; Tatang Talka Gani (Universitas Gadjah Mada, 2022)
Occipital stroke is associated with visual field defects and other visual perceptual deficits that might lead to detrimental effects on health-related quality of life. This study aimed to evaluate the possible association between systemic risk factors and the features of occipital stroke. It was a retrospective observational study involving patients diagnosed with occipital stroke in Dr. Yap Eye Hospital, Yogyakarta, Indonesia, between 2013 and 2014. A total of 72 patients with occipital stroke proven with CT/MRI who underwent detailed evaluation of ocular and systemic risk factors were included in this study. The patients were divided into two groups with or without risk factors. The risk factors were hypertension, diabetes mellitus, and cardiac diseases. The effect of risk factors on sex, age groups (≤40, >40 and ≤60, >60 y.o.), stroke lesions (left occipital, right occipital, bilateral), and visual field defects (homonymous hemianopia, homonymous quadrantanopia, and others) were analyzed. Out of 72 patients, there were 56 males (77.8 %), and 16 females (22.2 %), with a mean age of 58.46 ± 11.83 y.o. The study found there was a significant difference in age with risk factors compared with those without risk factors (p = 0.025), as well as visual acuity with age groups (p = 0.005) and stroke lesions (p = 0.024). Analysis of risk factors showed that hypertension was significantly correlated with stroke lesions, whereas cardiac disease was significantly associated with age groups (p<0.05). Predictive analysis was performed using a linear regression model, and it showed that risk factors could predict the occurrence of stroke lesions. In conclusion, patients’ systemic risk factors are significantly associated with the older onset of occipital stroke and lower visual acuity, although not significantly associated with stroke location and visual field defect characteristics.